Analysis of Education Character Policy to Realize Pancasila's Value to Elementary School Students - Dwi Maryani; Nur Cholidah; Febriyani Sulistyaningsih; Sutama; Achmad Fatoni (CV. Creative Tugu Pena, 2024)
This research analyzes character education policies to realize Pancasila's values in elementary school students. Using qualitative methods with case studies at some primary schools in Surakarta, data was collected through interviews, observations, and document analysis. Research results show that character education policies are implemented through the integration of Pancasila values into curricula, extracurricular activities, and teacher training. Collaboration between schools and parents is also effective in supporting student character education. However, challenges such as resource constraints and different understandings of character education remain. In conclusion, a character education policy based on Pancasila can effectively shape the character of elementary school students, with sustained support from all sides.